2021
DOI: 10.1007/s43546-021-00147-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trade, foreign direct investment, and economic growth on environmental quality and overshoot: a dynamic common correlation effects approach

Abstract: This study empirically investigates the effects of trade, foreign direct investment, and growth on environmental quality and sustainability. In order to attain the objective of the study, we adopt the novel dynamic common correlation effect technique that accounts for cross-sectional dependence. A panel of 109 countries from 1995 to 2016 was used for the study, based on availability of data. The results indicated that economic growth, trade openness, and FDI generally degrade the environment quality, while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Their findings revealed that the deteriorating impact of FDI on environmental quality is dependent on the indicators used and the extent of environmental degradation at the outset. Fonchamnyo et al (2021) empirically show within a global panel of 109 countries that economic growth, FDI and trade generally degrade the quality of the environment. In a study in South Asia, Murshed et al (2022) demonstrated dirty FDIs among other economic activities are seen to reduce the ecological footprint.…”
Section: Synopsis Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Their findings revealed that the deteriorating impact of FDI on environmental quality is dependent on the indicators used and the extent of environmental degradation at the outset. Fonchamnyo et al (2021) empirically show within a global panel of 109 countries that economic growth, FDI and trade generally degrade the quality of the environment. In a study in South Asia, Murshed et al (2022) demonstrated dirty FDIs among other economic activities are seen to reduce the ecological footprint.…”
Section: Synopsis Of Literaturementioning
confidence: 99%
“…As a key driver of growth and development identified within growth and development literature (Solow, 1956; Keynes, 1936; Becker, 1964; Samuelson and Solow, 1956), capital formation stands as the most viable source of growth within nations, and given that growth activities remain the mother activity for the emission of greenhouse gases into the atmosphere, the process of capital formation is primordial in tackling environmental quality enhancement goals. While foreign capital inflow into an economy spurs up the rate of domestic capital formation within the domestic economy and enhances growth and development, its accumulation has been identified as a key pollutant within the domestic economy and has been the root of major debates in the past decade (Murshed et al , 2022; Arogundade et al , 2022; Nathaniel et al , 2020; Fonchamnyo et al , 2021). If the inflow of foreign capital and its influence on the quality of the environment have been a focal point of major economic discussion in the past decade, then that of domestic capital accumulation has received relatively little attention (Yang and Khan, 2021; Fadly, 2019; Zhang et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Driscoll/Kraay strategy was employed after the ordinary least square (OLS), which minimizes only the sum squared residual. Following the Frees cross‐sectional dependence test presented in Table 1, indicating the presence of cross‐sectional dependence in the OLS estimates presented in Table 3, I preferred the Driscoll/Kraay strategy as its main strength is to account for cross‐sectional dependence (see Fonchamnyo et al, 2021; Nchofoung et al, 2021).…”
Section: Methodological Strategymentioning
confidence: 99%
“…In the presence of dependence in the cross‐sections, nonparametric corrections for the cross‐sectional dependence are best addressed by the Driscoll/Kraay technique (Fonchamnyo et al, 2021). Following the Frees cross‐sectional dependence test, reported in Table 2, I reject beyond the critical value (1%) with the assumptions of cross‐sectional independence.…”
Section: Methodological Strategymentioning
confidence: 99%